The Role of Idea Generation in Enhancing the Relationship Between Strategic Orientation and Entrepreneurial Performance: A Field Study of a Sample of Industrial Production Companies in Khartoum State - Elkhidir, Elsheikh Mohammed; Basheer, Basheer Eltahir; Nsibi, Helmi Mohamed; Souissi, Anis Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to investigate the effect of idea generation on the relationship between strategic orientation and entrepreneurial performance in industrial production companies in Khartoum state. The research problem was to question to what extent idea generation affects the relationship between strategic orientation and entrepreneurial performance.The study used a questionnaire as the main tool for collecting data, and the study population consisted of senior management and middle management of 12 Sudanese companies, with a sample of 210 respondents. The study also used the descriptive analytical approach.The results of the study showed that idea generation moderates the relationship between strategic orientation and entrepreneurial performance, where idea generation enhances the relationship between strategic orientation and entrepreneurial performance when the strategic orientation is oriented towards innovation and risk-taking.The study concluded that industrial production companies in Khartoum state should focus on creating a supportive environment for creativity and encouraging employees to participate in the decision-making process. The study also recommended that companies focus on developing employees' skills in the field of idea generation and innovation.
Keywords: strategic orientation; entrepreneurial performance; idea generation; innovation; risk-taking